2014
DOI: 10.1002/ijc.28707
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-224 inhibits progression of human prostate cancer by downregulating TRIB1

Abstract: Our previous microarray data showed that microRNA-224 (miR-224) was downregulated in human prostate cancer (PCa) tissues compared with adjacent benign tissues. However, the underlying mechanisms by which miR-224 is involved in PCa remain unclear. In this study, we identified TRIB1 as a target gene of miR-224. Forced expression of miR-224 suppressed PCa cell proliferation, invasion and migration, and promoted cell apoptosis by downregulating TRIB1. Moreover, the expression level of miR-224 in PCa tissues was ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 48 publications
2
102
1
1
Order By: Relevance
“…It has been reported that miR-224 was up-regulated in a number of solid tumors, including hepatocellular carcinoma (31,32), CRC (33), and breast cancer (34), and plays an oncogenic role by targeting API5, SMAD4, PHLPP1, PHLPP2, and RKIP. Inversely, miR-224 plays a tumor-suppressive role in prostate cancer by targeting TPD52 and/or TRIB1 (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miR-224 was up-regulated in a number of solid tumors, including hepatocellular carcinoma (31,32), CRC (33), and breast cancer (34), and plays an oncogenic role by targeting API5, SMAD4, PHLPP1, PHLPP2, and RKIP. Inversely, miR-224 plays a tumor-suppressive role in prostate cancer by targeting TPD52 and/or TRIB1 (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…6,7) Importantly, TRB1 is also found to be overexpressed in solid tumors, including prostate cancer, 8,9) thyroid cancer, 10) ovarian cancer, 11) and colorectal cancer. 12) In prostate cancer, Mashima et al have shown that TRB1 is a critical factor for cancer cell stemness and tumor propagating through expression of the endoplasmic reticulum chaperone GRP78.…”
Section: Discussionmentioning
confidence: 99%
“…4,5) TRB1 is also found to be overexpressed in solid tumors, including prostate cancer, 8,9) thyroid cancer, 10) ovarian cancer, 11) and colorectal cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, TRIB1 is involved in prostate cancer cell survival. Recently, it was reported that the TRIB1 expression was also regulated by a microRNA (miR-224) in prostate cancer and the TRIB1 upregulation was significantly associated with poor biochemical recurrence-free survival of patients with prostate cancer (35). These data suggest that TRIB1 could be a rational therapeutic target in prostate cancer.…”
Section: Trib1 and Grp78 As Therapeutic Targets Of Prostate Cancermentioning
confidence: 94%